The Drug Court Team and Discretionary Decision-Making: A Mixed-Methods Examination of Sanctioning Responses to Continued Participant Alcohol and Other Drug Use. (February 2021) - Gibbs, Benjamin R.; ten Bensel, Tusty; Doyle, Madison K.; Wakefield, William
Drug courts attempt to gain participant compliance and alcohol and other drug (AOD) use abstinence through a strategy of moderate and progressive sanctioning, but its discretionary application possesses the capacity for disparity across participants and behaviors. The purpose of this study was to examine the drug court team's (DCT) discretionary use of sanctions in response to continued participant AOD use. A mixed-methods approach was used for analyzing agency data ( n = 1, 032) and interviews of five members of the DCT. Data were collected from an adult felony drug court over a 6-year period (2008–2013) and use to answer the following research question: "What participant characteristics and program performance measures affected sanctioning outcomes?" We found that offender attributes did play a role in the sanctioning decision, but program performance measures were stronger predictors of sanction type.